Faktor Psikologi Sebagai Risiko Utama Ide Bunuh Diri pada Remaja di Kota Rengat Kabupaten Indragiri Hulu - Nur Aulia; Yulastri Yulastri; Heppi Sasmita (FORIKES, 2020)
The high incidence of suicide, especially in this age group in which the teen years may be one time the vulnerability to suicidal ideation. Data from the National Commission for Child Protection in Indonesia of suicides that occurred with the youngest is 13 years old. This can occur due to various risk factors for teen suicide include psychological factors. This study aims to identify suicidal ideation relationship with risk factors for suicide in adolescents. Analytical research design was correlation with cross-sectional approach. Sample 365 adolescents with proportional random sampling. Data were analyzed using logistic regression test. The results showed the number of adolescent suicidal ideation is high. There was a relationship of psychological factors with suicidal ideation (p